Ultrasound-assisted acid hydrolysis of cassava (Manihot esculenta) bagasse: Kinetics, acoustic field and structural effects - Polachini, Tiago Carregari [UNESP] (2021)
Improving the actual acid hydrolysis of cassava bagasse (CB) with the assistance of high-intensity ultrasound (US) was aimed in comparison with mechanical agitation (AG). The kinetics of reducing and total sugar release were mathematically modeled. The acoustic field characterization and apparent viscosity of the suspensions were correlated. Moreover, microscopic analyses (visible, fluorescence and polarized light) were carried out to identify changes produced by the treatments. Both AG and US-treatments showed themselves to be effective at hydrolyzing CB. However, US-experiments reached equilibrium in the reducing sugar release process earlier and obtained slightly higher values of total sugars released. The Naik model fitted the experimental data with good accuracy. A greater loss in the birefringence of the starch granules and the degradation of lignocellulosic matter was also observed in US-assisted hydrolysis. The actual acoustic power applied was reduced after hydrolysis, probably due to the increase in the apparent viscosity of the resulting suspensions.